ANALISIS PENGARUH IPM, UPAH MINIMUM, TPT DAN BANTUAN SOSIAL TERHADAP TINGKAT KEMISKINAN DI PROVINSI JAWA TIMUR TAHUN 2017-2022 - Riyandini, Shafa (Journal of Development Economic and Social Studies, 2024)
Poverty is a social problem that arises in economic development and can cause other problems. Therefore, there is a need for solutions to overcome the problem of poverty. This study aims to determine the role of Human Development Index (HDI), Open Unemployment Rate, minimum wage and social assistance spending on poverty rate in East Java. The sample of this study is 34 regencies and cities in East Java Province during 2017-2022. In this study, only 34 districts and cities were used because there were two cities that did not have the realization of social assistance spending. The data used in this study is secondary data sourced from BPS and DJPK of the Ministry of Finance. The method used is panel data regression with FEM (Fixed Effect Model). The results of this study show that each HDI has a significant negative effect and TPT has a significant positive effect on the poverty rate in East Java Province in 2017-2022. Meanwhile, the Minimum Wage and Social Assistance respectively have no significant effect on the poverty rate in East Java Province in 2017-2022.